2018
DOI: 10.1017/s0031182017002359
|View full text |Cite
|
Sign up to set email alerts
|

Differential virulence of camel Trypanosoma evansi isolates in mice

Abstract: This study assessed the virulence of Trypanosoma evansi, the causative agent of camel trypanosomiasis (surra), affecting mainly camels among other hosts in Africa, Asia and South America, with high mortality and morbidity. Using Swiss white mice, we assessed virulence of 17 T. evansi isolates collected from surra endemic countries. We determined parasitaemia, live body weight, packed cell volume (PCV) and survivorship in mice, for a period of 60 days' post infection. Based on survivorship, the 17 isolates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 40 publications
9
28
0
Order By: Relevance
“…Parasitaemia progression among Tbr isolates assigned to different virulence classes on the basis of survival time were significantly different. This finding is in agreement with previous studies in which virulence of different species of trypanosomes was characterised using parasitaemia, intensity of anaemia (PCV) and weight loss experienced by the host during the infection period [24]. In our study, parasitaemia of isolates in the very-acute virulence class was represented by a single wave whereas the acute, sub-acute and chronic virulence classes were represented by two waves.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Parasitaemia progression among Tbr isolates assigned to different virulence classes on the basis of survival time were significantly different. This finding is in agreement with previous studies in which virulence of different species of trypanosomes was characterised using parasitaemia, intensity of anaemia (PCV) and weight loss experienced by the host during the infection period [24]. In our study, parasitaemia of isolates in the very-acute virulence class was represented by a single wave whereas the acute, sub-acute and chronic virulence classes were represented by two waves.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with observations by [36] who reported that acute infection of mice with Trypanosoma cruzi was characterized by an exponential growth of parasites and high mortality accompanied by anemia. A similar observation was made by [24] in mice infected with Trypanosoma evansi . In contrast, anaemia in mice infected with clones in the other various classes of virulence (acute, sub-acute and chronic) stabilized or recovered characteristic of the chronic phase anaemia [37].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations